2010
DOI: 10.1007/s00520-010-1031-6
|View full text |Cite
|
Sign up to set email alerts
|

Problems in transition and quality of care: perspectives of breast cancer survivors

Abstract: Purpose We conducted a qualitative study to explore breast cancer survivors’ perceptions and attitudes about their current healthcare utilization, screening, and information needs. Methods We completed eight focus groups of breast cancer survivors. We included women, adult survivors, with an initial diagnosis of breast cancer in the year 2000, treated, and without a recurrence as per medical record. To analyze transcripts, we used grounded theory methods, wherein unexpected themes and direct answers emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…Survivors in the present study also reported frequent guilt, which influenced their decisions not to seek care when experiencing aftereffects of treatment. A recent study also found that bc survivors report guilt upon visiting cancer specialists and taking them away from patients with active cancer 23 . Feelings of guilt may be mitigated by ensuring that survivors have a better understanding of their post-treatment concerns and of the goals for quality follow-up care (for example, preventing or managing morbidity).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Survivors in the present study also reported frequent guilt, which influenced their decisions not to seek care when experiencing aftereffects of treatment. A recent study also found that bc survivors report guilt upon visiting cancer specialists and taking them away from patients with active cancer 23 . Feelings of guilt may be mitigated by ensuring that survivors have a better understanding of their post-treatment concerns and of the goals for quality follow-up care (for example, preventing or managing morbidity).…”
Section: Discussionmentioning
confidence: 95%
“…The most common concerns about fp-led care involved the practitioner's knowledge and competencies related to cancer care and the ability to rapidly access specialist care if needed. Concerns on the part of bc survivors about their fp's knowledge of and ability to provide follow-up care has recently been reported by others, as has their preference to receive follow-up care from cancer specialists 23,28 . However, our findings indicated that when the fp played an active role throughout the course of a survivor's diagnosis and treatment, that survivor was much more likely to trust the fp's ability to provide high-quality follow-up care.…”
Section: Current Oncology-volume 19 Number 6 December 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Medical oncologists have described a sense of responsibility during the follow-up period with respect to long-term toxicities and the survivor's compliance with ongoing therapies (for example, endocrine therapy) 24 ; other oncologists have questioned the ability of pcps to provide cancer-related care for survivors 25,26 . On the other hand, survivors are often confused over who is primarily responsible for cancer follow-up care [27][28][29] and uncertain about whether community-based providers have the expertise required to manage cancer follow-up 22,30 , both of which can contribute to concerns about discharge after treatment. The fact that follow-up guidelines often do not make specific recommendations about who should provide follow-up care might also contribute to a lack of role clarity for providers.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors report a need to have information that they can understand, 34 but also strategies to manage symptoms, prescriptions for health promotion, and help in the process of integrating the experience into one's life after treatment. 12,21,35 Those BCS who report higher symptom burden, symptom distress, and perceive inadequate information to manage symptoms and to cope with the transition from treatment to survivorship are at higher risk for distress and poorer QOL outcomes. 34,35 Most providers follow clinical practice guidelines recommending that BCS have a provider visit with a physical examination every 3 months in the first year, which translates into approximately four visits.…”
Section: Recovery Patterns Across the Trajectory Of Breast Cancer Surmentioning
confidence: 98%